Investigation of Dietary Habits and Lifestyle in relation to Diabetes Mellitus Type II among Private-Sector Employees of Lahore: A Cross-Sectional Study - Muhammad Imran Hussain, Fatima Naveed, Momina Sheikh, Minahil Arif, Sahaab Maqsood, Areeba Yasir, Huba Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Although some studies have shown the association between dietary patterns and the risk of type 2 diabetes mellitus in a general population but the associations in Pakistan have been rarely studied to date. Aim: To characterize the dietary patterns and lifestyle of private sector employees in Lahore adults aged above 25 to evaluate the relationship of dietary habits, and lifestyle with the incidence of type 2 diabetes. Methodology: A cross-sectional study was conducted on the private sector employees of Lahore, Pakistan. Two hundred and sixteen people participated in it and each provided their informed consent for data collection on their demographic, physical and biochemical characteristics along with the information on lifestyle and dietary patterns. Result: According to the observations from our study among the private sector employees in relation to their dietary habits, lifestyle and physical activity almost 174 private sector employees are diabetic out of which 42 are pre-diabetic.Their dietary intake was assessed using FFQ. The results show that diabetic people are taking more carbohydrates, saturated, trans-fats and red meat. Furthermore, pre-diabetic people are consuming high processed foods which contain more fats, calories and sugar without nutritional value. Conclusion: We have found that dietary habit, and lifestyle of private sector employees was associated with increased risk of Type 2 Diabetes Mellitus. As a result, in order to stop or reduce the prevalence of type 2 diabetes, it is necessary to promote healthy eating or dietary habits and physical activity to improve their lifestyle. Keywords: Cross-sectional study, informed consent, dietary intake, Diabetes Mellitus, FFQ, pre-diabetic.